Recent advances in macrophage-targeted nanoparticle drug delivery platforms for treating synovitis in rheumatoid arthritis - Hu Wanhua, Xu Yizhou, Bai Zhenglin, Wang Zeyu (Xin yixue, 2024)
Rheumatoid arthritis （RA） is a systemic autoimmune disease characterized by chronic and erosive polyarthritis. The core pathological changes involve persistent synovial inflammation and angioproliferation，leading to the destruction of joint cartilage and bone. The etiology and pathogenesis of RA remain unclear and complex. Despite decades of accumulated evidence and experience in the treatment of RA，there are currently no definitive methods to reverse RA joint tissue damage. Nanoparticle drug delivery platforms，as systems based on nanomaterials for drug delivery，are designed to improve drug distribution，enhance therapeutic effects，and reduce drug-related toxic side effects. This review focuses on the pathogenesis of synovitis in RA and explores the application and potential of macrophage-targeted nanoparticle drug delivery platforms in the prevention and treatment of RA.